Hemofiltration and peritoneal dialysis in infection-associated acute renal failure in Vietnam. - Phu, N; Hien, T; Mai, N; Chau, T; Chuong, L; Loc, P; Winearls, C; Farrar, J; White, N; Day, N (2002)
BACKGROUND: In some parts of the world, peritoneal dialysis is widely used for renal replacement in acute renal failure. In resource-rich countries, it has been supplanted in recent years by hemodialysis and, most recently, by hemofiltration and associated techniques. The relative efficacy of peritoneal dialysis and hemofiltration is not known. METHODS: We conducted an open, randomized comparison of pumped venovenous hemofiltration and peritoneal dialysis in patients with infection-associated acute renal failure in an infectious-disease referral hospital in Vietnam. RESULTS: Seventy adult patients with severe falciparum malaria (48 patients) or sepsis (22 patients) were enrolled; 34 were assigned to hemofiltration and 36 to peritoneal dialysis. The mortality rate was 47 percent (17 patients) in the group assigned to peritoneal dialysis, as compared with 15 percent (5 patients) in the group assigned to hemofiltration (P=0.005). The rates of resolution of acidosis and of decline in the serum creatinine concentration in the group assigned to hemofiltration were more than twice those in the group assigned to peritoneal dialysis (P<0.005), and renal-replacement therapy was required for a significantly shorter period. In a multivariate analysis, the odds ratio for death was 5.1 (95 percent confidence interval, 1.6 to 16) and that for a need for future dialysis was 4.7 (95 percent confidence interval, 1.3 to 17) in the group assigned to peritoneal dialysis. The cost of hemofiltration per survivor was less than half that of peritoneal dialysis, and the cost per life saved was less than one third. CONCLUSIONS: Hemofiltration is superior to peritoneal dialysis in the treatment of infection-associated acute renal failure.